Determinants of Preeclampsia Among Pregnant Women in Public Hospitals of Wolaita and Dawuro Zones, Southern Ethiopia: A Case?Control Study - Abiyot Wolie Asres; Wakgari Binu Daga; Serawit Samuel; Getachew Asmare Adella; Shimelash Bitew Workie; Abinet Desalegn (Mary Ann Liebert, 2022)
Introduction: Preeclampsia is a leading cause of maternal and fetal morbidity and mortality in Ethiopia. It is defined by the onset of new hypertension (HTN) and proteinuria in the second trimester of pregnancy. There is a research gap in the study area and there is an inconsistency of findings in previous studies. Therefore, this study aimed to determine the factors of preeclampsia among pregnant women in public hospitals. Methods and Materials: An institution-based unmatched case?control study was conducted in public hospitals in Wolaita and Dawuro Zones from February 1 to June 26, 2021. Women who were diagnosed with preeclampsia were cases, while those who did not have it were controls. They were selected using a consecutive sampling method. Descriptive statistics and logistic regression were done by STATA. Results: A total of 349 cases and 698 controls participated in this study. The average age of the cases and controls was 26.1???4.6 standard deviation (SD) and 24.6???4.8 SD years, respectively. The determinants of preeclampsia in this study were a family history of HTN (adjusted odds ratio [AOR?=?11.5; 95% confidence interval, CI: 6.46?20.41], family history of diabetes mellitus [AOR?=?2.1; 95% CI: 1.10?3.90], having two or multiple pregnancies [AOR?=?6.33; 95% CI: 2.28?17.51], primigravida [AOR?=?1.49; 95% CI: 1.01?2.21], and being gravida 5?9 [AOR?=?2.47; 95% CI: 1.34?4.58]). Conclusion: In this study, family history of HTN, family history of diabetes mellitus, history of preeclampsia, primigravida, and multiple gestation pregnancies were the determinants of preeclampsia. As a result, health care providers should pay special attention to pregnant women with a family history of HTN, primigravida, and two or multiple gestation pregnancies during antenatal care follow-up.